Canva-Based Teaching Material Creation Training to Develop Teacher Competencies - Sumartini, Tina Sri; Silvia, Syifa; Wahyuni, Widi; Apriliani, Yosi Khosilam (Indonesian Journal of Community Empowerment (IJCE), 2025)
Many teachers still face difficulties in utilizing technology, making training like this highly relevant. The lecture method provides an introduction to the Canva application and the importance of creating engaging teaching materials in the digital age. The lecture includes an explanation of Canva's main features, registration, and navigation within the application. The results and discussion of this training activity indicate that the use of technology, particularly applications like Canva, can be a very effective tool in teacher professional development. Competence in creating digital-based teaching materials is becoming increasingly important in 21st-century education, where information and communication technology skills are highly needed. While the Canva application has shown significant progress, teachers still face challenges in implementing technology in the classroom. Some teachers reported difficulties integrating digital teaching materials with the existing curriculum and overcoming the limitations of their schools' technological infrastructure. More innovative and responsive education to the needs of the digital age is expected to foster a better learning experience for students. Suggestions for implementing a project-based learning approach in training are presented.